The Impact of Institutionalization and the Application of Alternative Forms of Child Protection in Greece: A Conceptual Review - Farmakopoulou, Ignatia; Baltsioti, Vasiliki (Technium Education and Humanities, 2024)
This research paper provides a critical analysis of the Greek child protection system, focusing on the pressing need to transition from institutionalized care to alternative, family-based care solutions. Acknowledging the negative psychosocial and developmental effects of institutionalization, particularly for children with disabilities, the paper presents empirical evidence that underscores the urgency for reform. Historical and contemporary perspectives on child protection are explored, alongside the importance of legislative and community support for de-institutionalization efforts. The study advocates for a systematic overhaul to align the Greek system with international child welfare trends, including the promotion of foster care and adoption. By evaluating the existing legislative landscape, social attitudes, and psychological frameworks, the paper outlines the detrimental impact of institutional care on children’s cognitive, emotional, and behavioral outcomes, calling for an inclusive national policy that privileges the well-being and integration of all vulnerable minors within a family-oriented context. The research concludes with recommendations for future work in exploring the practical implementation of family-based care models and assessing the long-term outcomes for children shifted from institutional settings to foster homes.